HashiCorp infrastructure automation Terraform associate exam guide : effectively manage infrastructure as code to scale your infrastructure across AWS, Azure, and Google Cloud - Mishra, Ravi (Packt Publishing, 2021)
Leverage Terraform's capabilities to reuse code, write modules, automate deployments, and manage infrastructure state Key Features Perform complex enterprise-grade infrastructure deployments using Terraform v1.0, the latest version of Terraform Learn to scale your infrastructure without introducing added deployment complexities Understand how to overcome infrastructure deployment challenges Book Description Terraform is a highly sought-after technology for orchestrating infrastructure provisioning. This book is a complete reference guide to enhancing your infrastructure automation skills, offering up-to-date coverage of the HashiCorp infrastructure automation certification exam. This book is written in a clear and practical way with self-assessment questions and mock exams that will help you from a HashiCorp infrastructure automation certification exam perspective. This book covers end-to-end activities with Terraform, such as installation, writing its configuration file, Terraform modules, backend configurations, data sources, and infrastructure provisioning. You'll also get to grips with complex enterprise infrastructures and discover how to create thousands of resources with a single click. As you advance, you'll get a clear understanding of maintaining infrastructure as code (IaC) in Repo/GitHub, along with learning how to create, modify, and remove infrastructure resources as and when needed. Finally, you'll learn about Terraform Cloud and Enterprise and their enhanced features. By the end of this book, you'll have a handy, up-to-date desktop reference guide along with everything you need to pass the HashiCorp Certified: Terraform Associate exam with confidence. What you will learn Effectively maintain the life cycle of your infrastructure using Terraform 1.0 Reuse Terraform code to provision any cloud infrastructure Write Terraform modules on multiple cloud providers Use Terraform workflows with the Azure DevOps pipeline Write Terraform configuration files for AWS, Azure, and Google Cloud Discover ways to securely store Terraform state files Understand Policy as Code using Terraform Sentinel Gain an overview of Terraform Cloud and Terraform Enterprise Who this book is for This book is for experienced cloud engineers, DevOps engineers, system administrators, and solution architects interested in developing industry-grade skills with Terraform. You will also find this book useful if you want to pass the HashiCorp Certified: Terraform Assoc ...